An Assessment of External Price Competitiveness for Mozambique - Vitek, Francis (IMF Working Papers; Working Paper ;, 2009)
This paper conducts an assessment of external price competitiveness for Mozambique. A variety of indicators suggest that Mozambique has recently lost external price competitiveness with respect to its major trading partners. Consistent with these indicators, an exchange rate assessment indicates that the metical is overvalued by 26 to 41 percent in real effective terms. If sustained, an overvaluation of this magnitude has the potential to retard economic growth and jeopardize external stability, calling for an adjustment of monetary policy to gradually restore external price competitiveness.